Plant growth-promoting bacteria in metal-contaminated soil: Current perspectives on remediation mechanisms - Wang, Yue; Narayanan, Mathiyazhagan; Shi, Xiaojun; Chen, Xinping; Li, Zhenlun; Natarajan, Devarajan; Ma, Ying (Frontiers in Microbiology, 2022)
Heavy metal contamination in soils endangers humans and the biosphere by reducing agricultural yield and negatively impacting ecosystem health. In recent decades, this issue has been addressed and partially remedied through the use of "green technology", which employs metal-tolerant plants to clean up polluted soils. Furthermore, the global climate change, enhances the negative effects of climatic stressors (particularly drought, salinity, and extreme temperatures), thus reducing the growth and metal accumulation capacity of remediating plants. Plant growth-promoting bacteria (PGPB) have been widely introduced into plants to improve agricultural productivity or the efficiency of phytoremediation of metal-contaminated soils via various mechanisms, including nitrogen fixation, phosphate solubilization, phytohormone production, and biological control. The use of metal-tolerant plants, as well as PGPB inoculants, should hasten the process of moving this technology from the lab to the field. Hence, it is critical to understand how PGPB ameliorate environmental stress and metal toxicity while also inducing plant tolerance, as well as the mechanisms involved in such actions. This review attempts to compile the scientific evidence on this topic, with a special emphasis on the mechanism of PGPB involved in the metal bioremediation process (plant growth promotion, metal detoxification/(im)mobilization/bioaccumulation/transformation/translocation) and deciphering combined stress (metal and climatic stresses) tolerance.